KESAHIHAN PEMERIKSAAN COMPLEX SPECIFIC COCKTAIL ANTIGEN TB (ESAT-6, CFP-10, MPT-64) METODE CEPAT IMMUNOCHROMATOGRAPHY PADA CAIRAN SEREBROSPINAL PASIEN MENINGITIS TUBERKULOSIS {Validity of Rapid Immunochromatography Complex Specific Cocktail Antigen TB (Esat-6, Cfp-10, Mpt-64) Using Cerebrospinal Fluid of Tuberculous Meningitis Patient} - Livia Noviani; Ida Parwati; Ganiem AR; Turbawati DK (INDONESIAN JOURNAL OF CLINICAL PATHOLOGY AND MEDICAL LABORATORY, 2015)
The early diagnosis of definite tuberculous meningitis (TBM) is very important in reducing its mortality. The current gold standard ofTBM relies on the isolation of M. tuberculosis from cerebrospinal fluid (CSF) either with direct staining or M. tuberculosis culture, but theseexamination have a low sensitivity due to the pausibasilary condition. Recently there is an assay using rapid Immunochromatography(ICT) cocktail antigen TB in CSF to diagnose TBM. This method can detect ESAT-6, CFP-10 and MPT-64 antigen as an important virulencefactor for the spreading of bacteria to extra pulmonary which is secreted by M. tuberculosis in CSF from TBM patient. The aim of thisstudy was to know the validity of rapid ICT cocktail antigen TB using CSF against MODS culture and acid-fast bacili as a gold standardto diagnose TBM by analyzing. This study iscarried out by a descriptive observational study using cross sectional study design. Thesubjects are patients who were diagnosed as suspected TBM based on Marais criteria and were obtained from the Department of NeurologyHospital Dr. Hasan Sadikin. The examination was done at the Clinical Microbiology Department of Clinical Pathology Dr. Hasan Sadikinhospital since January 2014 until May 2014. A total of 41 subjects which consisted of six (6) subjects with a definite diagnosis of TBM,26 with probable TBM and nine (9) with possible TBM were enrolled in this study. The result of this assay againts acid-fast bacili has the100% sensitivity, 64.1% specificity, 12.5% PPV, 100% NPV, LR(+) 2.78, LR(–)0 and 65.8% accuracy. The result of this assay againtsM. tuberculosis culture has the 83.3% sensitivity, 68.5% specificity, PPV 31.2%, NPV 96%, LR(+) 2.65, LR(–)0.24, accuracy 70.7% andprevalence ratio 7.8. Based on this study, it can be concluded that the validity of this assay againts acid-fast bacili has a high sensitivity,moderate specificity, low PPV, high NPV and moderate accuracy. The result of this assay againts M. tuberculosis culture has a moderatesensitivity and specificity, low PPV, high NPV and moderate accuracy.